Effectiveness Of Termination Of Employment For Efficiency Reasons - Rasji; Aurel Aprilia Annisya Trisetya (CV Rewang Rencang, 2024)
The employment relationship between workers and employers establishes labor protection aimed at ensuring balance without pressure from the stronger party. However, termination of employment for efficiency reasons often becomes controversial. This study aims to assess the effectiveness of termination of employment due to efficiency and the fulfillment of affected workers' rights. The research method employed is normative juridical with a statutory approach. The results indicate that ToE for efficiency is regulated under the Manpower Law but lacks a clear definition of efficiency. Amendments in the Job Creation Law permit termination of employment without company closure, sparking protests from workers. In practice, efficiency is often misused by companies to unilaterally terminate employment. Workers affected by termination of employment are entitled to severance pay, long service awards, and compensation for rights in accordance with applicable regulations. This analysis highlights the need for company financial audits to substantiate efficiency claims and the importance of transparency from employers. The study concludes that while efficiency-based termination of employment can be effective for companies, its implementation must balance worker interests and corporate sustainability to prevent injustices..